Cisplatin/5-Fluorouracil (5-FU) Versus Carboplatin/Paclitaxel Chemoradiotherapy as Definitive or Pre-Operative Treatment of Esophageal Cancer - Steber, Cole (Cureus, 2021)
Purpose To determine the efficacy and toxicity of two standard chemotherapy regimens used concurrent with radiation for the treatment of esophageal cancer: cisplatin/5-fluorouracil (5-FU) and carboplatin/paclitaxel. Materials and methods We prospectively reviewed records of 364 patients with histologically confirmed stage I to IVA esophageal cancer receiving chemoradiotherapy (CRT) with or without resection. All patients received surgical evaluation and imaging at presentation as well as following completion of their course of CRT. Treatment and prognostic variables were compared across the two chemotherapy regimens. Results We identified 261 patients treated with concurrent carboplatin/paclitaxel (n = 133) or cisplatin/5-FU (n = 128). Weight loss during CRT was lower in patients receiving carboplatin/paclitaxel (median: 7.0 pounds; 4.1% body weight) vs. cisplatin/5-FU (median: 11.0 pounds; 6.5% body weight) (p < 0.01). In 117 patients receiving trimodality therapy, post-operative death rates within one month of resection were similar. Pathologic complete response was better with carboplatin/paclitaxel vs. cisplatin/5-FU, 29.6% vs. 21.8% (p = 0.03), respectively. In the multivariable analysis, there was no association between chemotherapy regimen and overall survival (OS) or progression-free survival (PFS), though there was a trend toward improved OS with carboplatin/paclitaxel with a HR = 0.75 (p = 0.08). Further analysis revealed that trimodality therapy and stage were predictors for improved OS and PFS while female gender and grade predicted for improved PFS. Conclusions Carboplatin/paclitaxel was associated with decreased weight loss and improved pathologic response for trimodality patients when compared to cisplatin/5-FU. We observed no differences in OS, PFS, or post-operative death by chemotherapy regimen for both the entire cohort and trimodality patients.